FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN MAHASISWA DALAM SISTEM PERKULIAHAN PADA MASA COVID-19 DI ITB STIKOM BALI - Kadek Enny Rusmala Dewi; I Made Candiasa; Gede Indrawan (Media Bina Ilmiah, 2023)
This research aims to identify the significant factors that contributes on students’ satisfaction in the lecturing system in terms of service quality dimension, which include reliability, assurance, responsiveness, empathy and physical evidence (tangibles). This study employed a quantitative correlational approach with an ex post facto design. The population of this study consisted of 348 ITB STIKOM Bali Campus students in the academic year 2021/2022. Using the Slovin formula and proportional random sampling, a sample size of 186 is determined and selected. This study collects data regarding service quality and student satisfaction using questionnaires. The method of analysis employed is simple regression analysis and multiple regression. The results indicate that: (1) the reliability dimension contributes significantly to student satisfaction, (2) the assurance dimension contributes significantly to student satisfaction, and (3) the responsiveness dimension can contribute significantly to student satisfaction. (4) the empathy dimension contributes significantly to student satisfaction (5) The tangibles dimension contributes significantly to student satisfaction. (6) Concurrently, there is a substantial contribution. Service quality dimensions have a significant effect on student satisfaction (7), and empathy is the most influential service quality factor influencing student satisfaction in the lecture system during the Covid-19 pandemic (46.19%). The determination test revealed that 90.30% of student satisfaction was influenced by service quality dimensions, with the remaining 9.70% influenced by other variables.